Transforming Profane Space into Sacred: The Case of the Buka Luwur Tradition - Vivi Kurnia Putri; Purwanto, Edi; Rukayah, R. Siti; Sardjono, Agung Budi (Nature: National Academic Journal of Architecture, 2025)
The Buka Luwur tradition is a cultural ritual held annually on the 15th of Muharram in Kaliputu Village. This tradition serves as a form of respect to an ancestor, Mbah Depok Soponyono. The procession involves local community members who carry ritual items such as kain luwur (sacred cloth), offerings (sesajen), jenang (traditional porridge), and tumpeng (cone-shaped rice), all of which are considered cultural symbols. The ritual begins with a procession on foot from the main road of Kaliputu Village to the tomb of Mbah Depok Soponyono. This study aims to examine how the Buka Luwur ritual transforms public space into sacred space through meaningful cultural symbols that shape a temporary cultural space. A qualitative approach with a case study method was used, involving the subjective experiences of the local community. The findings reveal that the interaction between cultural symbols and collective community action can symbolically transform a space into a sacred one. Ritual elements such as kain luwur, offerings, jenang, tumpeng, and the procession route function as markers with deep spiritual, social, and cultural meaning for the community—signifying the construction of a temporary cultural space.